Exploring Service Quality and Customer Satisfaction in the Service Industry: A Mixed-Methods Analysis - Laksamana Amerta; Ishwari Madhavi (Journal on Economics, Management and Business Technology, 2023)
This research delves into the intricate dynamics between service quality and customer satisfaction within the diverse landscape of the service industry. Embracing a mixed-method approach, the study examines the correlation between perceived service quality dimensions and the resulting levels of customer satisfaction across various service sectors. Hypotheses proposing a positive relationship between service quality and satisfaction serve as guiding principles in exploring the multifaceted dimensions of this association. The methodology integrates quantitative analyses, including surveys and regression analysis, with qualitative insights derived from interviews and focus groups. Data analysis unravels potential correlations, nuanced variances, and unexpected influences shaping customer perceptions of service quality and satisfaction. Findings from the study contribute nuanced insights, revealing sector-specific nuances, non-linear relationships, and unforeseen influences on satisfaction levels. The practical implications drawn from these discoveries underscore the significance of tailored service strategies, employee empowerment, technology integration, and a relentless commitment to customer-centricity. The research concludes that the pursuit of superior service quality transcends immediate customer satisfaction, representing a commitment to organizational excellence and sustained growth within the competitive service industry. By leveraging the insights garnered, businesses can refine their service delivery approaches, foster enduring customer relationships, and carve pathways toward sustained success in meeting evolving customer expectations.